Theoretical aspects of human capital formation through human potential migration redistribution and investment process - Olha Podra; Liliia Kurii; Victor Alkema; Halyna Levkiv; Oleh Dorosh (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Our research is devoted to the investigation of theoretical aspects of human capital formation through human potential migration redistribution and investment process. This topic was chosen because in the modern conditions human potential development becomes one of basic factors of the competitiveness and economic growing of countries. Migration redistribution becomes an effective mean of indemnification of human potential losses, gives additional possibilities to its development financing, quantitative increase and additional innovative changes in the context of information society and knowledge-based economy development. The detailed analysis of the human potential development and implementation on the global labor market, the emergence of the migration cycle, and process of human potential transformation to capital that is able to provide the socio-economic and individual effects receiving was conducted in the article. Results of this study have theoretical and practical significance. They can be used as a basis for further scientific studies in this field and can be used by state institution in the direction of strategic management of human resources through the human potential migration redistribution and investment process that implies expansion of investment instruments, market infrastructure subjects development all this may provide the reception of material or status effects as a result of human potential capitalization in the labour market.
Keywords: J24; J20; G61; G62; 650; human potential; migration; human capital; investments; information society development